Proteomic Profiling of Plasma and Total Blood Exosomes in Breast Cancer: A Potential Role in Tumor Progression, Diagnosis, and Prognosis - Tutanov, Oleg; Proskura, Ksenia; Kamyshinsky, Roman; Shtam, Tatiana; Tsentalovich, Yuri; Tamkovich, Svetlana (Frontiers in Oncology, 2020)
Exosomes are directly involved in governing physiological and pathological conditions of an organism by transferring information (proteins, microRNA, etc.) from producing to receiving cells. We evaluated the influence of protein cargoes of exosomes from plasma, and exosomes from the total blood of healthy females (HFs) and breast cancer patients (BCPs), on crucial steps of tumor progression: EMT, cell proliferation, invasion, cell migration, stimulation of angiogenesis and immune response. We conducted a mass spectrometric analysis of proteomic content of exosomes isolated from samples using ultrafiltration and ultracentrifugation. Their nature has been verified using cryo-electron microscopy and flow cytometry. Bioinformatics analysis showed that 84% of common exosomal proteins were of cytoplasmic and vesicle origin. They perform functions of protein binding and signaling receptor binding, and facilitated the processes of the regulated exocytosis and vesicle-mediated transport. We observed that metabolism-related signaling pathways were enhanced in the exosome-mediated intracellular communication. Half of the identified exosomal proteins from blood of HFs and BCPs are involved in crucial steps of the tumor progression: EMT, cell proliferation, invasion, cell migration stimulation of angiogenesis, and immune response. Moreover, we revealed that proteomic profiles of exosomes from HF total blood were enriched with proteins inhibiting EMT, cell migration, and invasion. Tumor diagnostic/prognostic protein markers accounted for 47% of the total composition of cell-surface-associated exosomes (calculated as the difference between the total blood exosomes and plasma exosomes) from BCP blood. Breast cancer-associated proteins were equally represented in the blood cell-surface-associated exosomes and in the plasma exosomes from BCPs. However, hyper-expressed proteins predominate in the blood cell-surface-associated exosomes as compared to the plasma exosomes (64% vs. 14%). Using breast cancer proteins data from the Human Protein Atlas (HPA) (www.proteinatlas.org/), three favorable (SERPINA1, KRT6B, and SOCS3) and one unfavorable (IGF2R) prognostic protein markers were found in the BCP total blood exosomes. Further studies will be needed to determine whether identified new exosomal proteins from BCP blood are potential breast cancer diagnostic/prognostic markers or novel therapeutic targets.